Modernization, nationalism and the elite: the Genesis of Brazilian jiu-jitsu, 1905-1920 (Tempo e Argumento, 2011)
This article is based on a chapter of my dissertation entitled The Gracie Clan and the Making of Brazilian Jiu Jitsu: National Identity, Performance and Culture, 1905-1993. Itanalyzes the introduction, creolization, popularization and globalization of the martial art known as Brazilian jiu-jitsu, by examining the trajectory of theprincipal agents of these events, the Gracie family who reinvented the Japanese martial art by creating a complex, ritualistic hyper-masculinized life style, forged from the clash between tradition and modernity embed in violence “made in Brazil.” The article is divided in two sections in which I analyzed the introduction of Japanese jiu-jitsu as part of a turn-of- the-century global modernization. In the first part the narrative takes place in Rio de Janeiro in early twentieth century and examines the introduction of Japanese jiu-jitsu as modern school of physical education patronized by the military. This section is represented in the vignette “Round 1”. In the second part the narrative shifted to the Amazon where a modern school of jiu-jitsu was established as a result of a transnational encounter between a troupe of Japanese martial artists and a Scottish-Brazilian family. This section is represented in the vignette Round 2.
Keywords: modernization; identity; nationalism; race; performance